Managing Healthcare Projects Using DSDM and Agile Project Management A Comprehensive Guide for Professionals. - Kakumanu, Oswin (Oxford : Productivity Press, 2024)
Managing Healthcare Projects Using DSDM and Agile Project Management: A Comprehensive Guide for Professionals provides a comprehensive guide to implementing agile project management in healthcare.
Maintaining Agility and Flexibility in Complex Healthcare Systems -- 9. Managing Risks and Compliance in Healthcare Projects -- Identifying and Mitigating Risks Specific to Healthcare Projects -- Navigating Healthcare Regulations and Ensuring Compliance (e.g., HIPAA, GDPR, Local Regulations) -- Data Security Considerations in Agile Healthcare Projects -- 10. Fifteen Case Studies -- Examples of Healthcare Project Case Studies Managed Using DSDM and Agile -- Lessons Learned and Best Practices -- Conclusion -- The Future of DSDM and Agile in Healthcare Project Management
Description based upon print version of record.
Key Takeaways and Recommendations for Successful Implementation
Keywords: Systems integration; Health services administration